Let Us Rise: Dialectical Thinking, the Commodification of Labour Power, and the Legacy of the Socialist Party of Canada - Campbell, Peter (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2021)
Members of the Socialist Party of Canada (spc) played a prominent role in the labour revolt of 1919, the One Big Union, and the Winnipeg General Strike. The “failure” of all three has led labour historians to focus on the inability of the party to connect with Canadian workers, an inability fuelled by dogmatism, “impossibilism,” and the exclusion of women and workers of colour. This article turns this approach on its head, pointing out that these events have been unequalled in Canadian history, and seeks to explain why this should be so. It challenges the perception of the party as being wed to evolutionary thinking that caused its members to wait around for the revolution to happen. Instead, it reveals the powerful influence of the dialectical method developed by G. W. F. Hegel; its focus on human action was the philosophical underpinning of the spc’s relentless attack on the wage system and the capitalist system’s commodification of labour power. Far from being “metaphysical” or “otherworldly,” the spc’s insistence that workers must gain control of the product of their own labour spoke directly to them, including women and workers of colour. In the creation of the One Big Union, in the solidarity of the Winnipeg General Strike, and in the promise of the labour revolt of 1919, we find the legacy of a party committed to workers rising up.